Detection and identification of anaerobic microorganisms biochemically degrading lignin in İğneada floodplain forest - Özsefil, İbrahim Cem. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2022., 2022)
Lignocellulosic biomass, which is found in large amounts in nature and a significant part of it is considered as waste, is seen as one of the most promising source for green and renewable energy for various reasons. However, lignin prevents the lignocellulosic material from reaching its potential due to its recalcitrant structure. The anaerobic digestion of lignin by microorganisms seems to be the most viable option to overcome this obstacle. The aim of this thesis is to discover anaerobic microorganisms that can digest lignin from sediment and dune samples taken from two different regions (Hamam Lake and Bulanık Stream) of the İğneada floodplain forest in northwest Turkiye. Samples were enriched with alkaline lignin as a sole carbon source at 37oC with three incubation periods lasting a total of 150 days. Then, DNA of the samples was isolated and sequenced metagenomically by MinION. In addition, various physicochemical analyzes including biogas production, pH, gas composition, VFA production, VS removal, determination of lignin content were carried out to detect how the microbial community operates during the experiments. As a result of the thesis, the degradability capacity of lignin in an oxygen-free environment has been demonstrated by various parameters for both stations. According to metagenomic data, it was determined that some microbial phyla and species, in which the microbial community changed as the transfers progressed, became dominant. Consequently, microbial community members that may be responsible for lignin digestion have also been identified.
Keywords: İğneada (Kırklareli, Türkiye); Lignocellulose.